Local Development and Sale of Municipal Real Estate - Janina Kotlińska (Barometr Regionalny, 2018)
Local development is associated with investments, the implementation of which requires significant financial resources. Revenues are the primary source of these funds, but also own income or non-returnable funds from abroad. Thus, those local self-governments (LGU ) will develop, which actively and effectively participate in the real estate market, as well as those that will have the possibility to incur liabilities. The indicated conditions are closely related to the construction of an individual debt limit of LGU. In the study, attention was focused on the effects of changing the LGU debt limitation to the economy of municipal real estate in Poland — probably unintended by the legislature. Its purpose is to indicate that the new approach to LGU debt limitation: (1) encourages local government to sell municipal real estate and forced the analysis of the structure of municipal real estate in the aspect of having real estate, and (2) causes changes in the structure of municipal real estate and ways of using it. The statistical data from 2010–2016 are the background and confirmation of the theses and issues presented in the study. The considerations and figures presented in the study show that: (1) return revenues are primarily the source of financing local development, although in recent years a significant change is visible in this area, (2) the new LGU debt rule forces LGU to undertake actions aimed at selling property, (3) sales of municipal real estate is conditioned both by the potential buyer and the seller, (4) both the pool and the structure of municipal real estate is changing, which gives grounds to believe that in the face of many restrictions, it has a chance to become optimal in given conditions and time, and (5  ) the optimal structure of municipal real estate from the point of view of territorial self-government missions, the number and type of tasks performed by individual LGU, as well as their situation and financial conditions is different in each LGU, and it is difficult to assign a target status.